ПИСЕМНІ ВІДОМОСТІ ПРО ТИВЕРЦІВ І УЛИЧІВ (огляд джерел) (Zaporizhzhia Historical Review, 2021)
In the article represents all the known fund of written testimonies about the tivertzi and the ulitchi, the tribes who lived in the Carpathian – Black Sea – Region. This generalized vision of the point discovers some new perspctives for further studies of the origin, development and historical destiny of the mentioned tribes.